Political anomalies and web-based civil antibodies in Silvio Berlusconi’s Bel Paese - Navarria, Giovanni (RECERCA. Revista de Pensament i Anàlisi, 2012)
Italy’s complex history has produced some remarkable path-breaking experiences and quite a few dangerous anomalies (such as Silvio Berlusconi’s media driven political regime), but it has also made the country the perfect ground for testing experimental antibodies that can contrast such anomalies. One of these antibodies is the web-based civil society orbiting around the blog Beppegrillo.it. This article argues that the story of such community shows the path to follow for the Italian civil society. Grillo and his fellow bloggers in fact have so far demonstrated that new communication media have the potential to free citizens’ from control and at the same time increase their capacity to keep a close watch on power. La compleja historia de Italia presenta algunas experiencias innovadoras así como bastantes anomalías peligrosas (por ejemplo el régimen mediáticamente controlado de Silvio Berlusconi), pero ha convertido también el país en el territorio perfecto para el surgimiento de anticuerpos que pueden contrastar dichas anomalías. Uno de estos anticuerpos es la sociedad civil basada en la web que gira en torno al blog Beppegrillo.it. Este artículo argumenta que la historia de dicha comunidad muestra el camino a seguir para la sociedad civil italiana. Grillo y el conjunto de sus seguidores blogeros han demostrado de hecho que nuevos medios de comunicación tienen el potencial de liberar a los ciudadanos del control y a su vez aumentar su capacidad para mantener estrechamente vigilado al poder.